Leishmaniasis: new approaches to disease control. Issue 7385 (15th February 2003) - Davies, Clive R; Kaye, Paul; Croft, Simon L; Sundar, Shyam
Abstract : Leishmaniasis is one of the major infectious diseases affecting the poorest regions of the world, but new developments in diagnosis, treatment, and control offer some fresh hope